Jacalin–carbohydrate interactions: distortion of the ligand molecule as a determinant of affinity. (1st February 2015) - Abhinav, K. V.; Sharma, Kaushal; Swaminathan, C. P.; Surolia, A.; Vijayan, M.
<x xml:space="preserve">Abstract</x> Jacalin is among the most thoroughly studied lectins. Its carbohydrate‐binding site has also been well characterized. It has been postulated that the lower affinity of β‐galactosides for jacalin compared with α‐galactosides is caused by steric interactions of the substituents in the former with the protein. This issue has been explored energetically and structurally using different appropriate carbohydrate complexes of jacalin. It turns out that the earlier postulation is not correct. The interactions of the substituent with the binding site remain essentially the same irrespective of the anomeric nature of the substitution. This is achieved through a distortion of the sugar ring in β‐galactosides. The difference in energy, and therefore in affinity, is caused by a distortion of the sugar ring in β‐galactosides. The elucidation of this unprecedented distortion of the ligand as a strategy for modulating affinity is of general interest. The crystal structures also provide a rationale for the relative affinities of the different carbohydrate ligands for jacalin.